2016
DOI: 10.18006/2016.4(issue6).662.669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen and sulfur on the quality of the cotton fiber under mediterranean conditions

Abstract: Agronomic practices significantly influence the productivity and quality of cotton plant. Present study was undertaken to evaluate the effect of nitrogen and sulfur fertilizer application on the fiber quality of cotton, during the year 2011/2012 and 2012/2013 under Mediterranean environmental conditions. All the treatments were laid in randomized complete block design in factorial arrangement each treatment were replicated thrice. Five rates of nitrogen (0, 60, 120, 180 and 240 kg ha -1 ) and five rates of sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Fiber quality parameters such as fiber micronaire, length, and strength did not show any response to N rate or placement in this study (Table 4). Many studies have reported general improvement of fiber quality parameters with increasing N rate (Bauer & Roof, 2004;Gormus & El Sabagh, 2016;Read, Reddy, & Jenkins, 2006). Saleem, Bilal, Awais, and Shahid (2010) however, concluded fiber quality was more influenced by variety choice than N fertilization rate in their study that evaluated three Pakistani cotton varieties.…”
Section: Discussionmentioning
confidence: 94%
“…Fiber quality parameters such as fiber micronaire, length, and strength did not show any response to N rate or placement in this study (Table 4). Many studies have reported general improvement of fiber quality parameters with increasing N rate (Bauer & Roof, 2004;Gormus & El Sabagh, 2016;Read, Reddy, & Jenkins, 2006). Saleem, Bilal, Awais, and Shahid (2010) however, concluded fiber quality was more influenced by variety choice than N fertilization rate in their study that evaluated three Pakistani cotton varieties.…”
Section: Discussionmentioning
confidence: 94%
“…Journal of Experimental Biology and Agricultural Sciences http://www.jebas.org The integrated management practices have an influence the productivity in various crops under different environmental conditions (EL Sabagh et al, 2015b;EL Sabagh et al, 2016c;Gormus et al, 2016a;Gormus et al, 2016b andGormus et al, 2017).…”
Section: ____________________________________________________________mentioning
confidence: 99%